Materialidades audiovisuais : uma proposta de leitura discursiva para o ensino médio - Burach, Caroline Adriana Mendes (2016)
This work has the objective to present a discursive read proposal, intended for the 3rd year of high school, based on two cinematic materialities: the short movie Vida Maria and the documentary Severinas grounded in the concepts proposed by Michel Pêcheux (1988) and Orlandi (1982). The researcher that gives continuity and present new prospects to the Pecheux Discourse Analysis on the French line research from now on. The Discourse Analysis takes as discourse the effects in a sense created by the relation between individuals. This relation is not just a relation among empiric individuals, but socio-ideological positions build on the historical movements. In circumstances of moments of my research trajectory, firstly undertaking previous analyses to the readout about the choice visual materialities to compose our reading proposal intended for the 3rd year of high school (SERRANI, 2005; BAGHIN-SPINELLI, 1998). Attempting to work with the read possibilities and to formulate activities in which to work the verbal and visual imbrication constitutive of the selected material of the selected material. My reading proposal of video (a short movie and a documentary), is a guidance to high school teachers. Consisting of reading practical of images from the selected cinematic materialities. To study from the which one work the "reading possibilities" given possible interpretations, including as well the movements of the sliding of sense. The formulated activities are planned to give consequences to the opacity of say/image. Based on the construction of likely paraphrases from the scenes records captured from the cinematic materialities. Giving the possibility to relativize the evidence of a unique and gauzy sense, listening to the possible movements. First of all the investment in the Discourse Analysis concepts and the multidimensional-discursive proposal of Serrani (2005) allowed me an analytical anchoring. Where the activities of reading here proposed will promote changes regarding the way to see the language as a mere communication instrument. All afford made aims to create practices and actions of reading where the opacity and contradiction of image became more productive and significant aspects, thinking in possibles of referrals to the language teacher.